A PE / EPDM high thermal conductivity insulation material for EV charging cables and a preparation method thereof
By forming a dual continuous structure in Sanyuanye Rubber and polyethylene, and distributed thermal fillers in Sanyuanye Rubber, the problem of insufficient thermal conductivity in the charging cable of new energy vehicle is solved, and high thermal conductivity is achieved. The composite material of high insulation and good mechanical properties is suitable for new energy vehicle charging cables.
Patent Information
- Application Number
- CN202310132763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The thermal conductivity of polymer materials in the charging cables of new energy vehicles is insufficient, resulting in an increase in the cable temperature during charging, affecting service life and safety.
Through the formula design, the triaphic ethylene rubber and polyethylene form a dual continuous structure, and control the preparation process, so that the heat conduction filler is distributed in the continuous phase of the triadi ethylene rubber, thereby forming an efficient thermal conductivity.
It significantly improves the thermal conductivity of composite materials while maintaining mechanical properties and insulation properties, meeting the performance requirements of the insulation layer of wires and cables, and is suitable for DC charging pile cables for new energy vehicles.
Smart Images

Figure CN116003921B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of thermally conductive composite materials, and in particular relates to a PE / EPDM high thermal conductivity insulating material for EV charging cables and a preparation method thereof. Background Art
[0002] At present, the number of new energy vehicles in the domestic market is growing rapidly. However, compared with traditional fuel vehicles, new energy vehicles still have the problem of slow charging speed. In order to increase the charging speed, it is necessary to increase the charging current of the cable, but it will also cause the cable to generate too much heat during the charging process. At present, the polymer materials used in the insulation and sheath layers of the cables have the problem of low thermal conductivity, which causes the heat generated by the cable during the charging process to be unable to be transferred out in time, which in turn causes the cable temperature to rise, affecting the service life and safety during use. Therefore, the thermal conductivity of the cable material of the new energy charging pile has become a key problem that limits the charging speed of new energy vehicles.
[0003] EPDM rubber and polyethylene are commonly used polymer materials in cable insulation and sheath layers, with good anti-aging, heat resistance and electrical insulation properties. As traditional polymer materials, their thermal conductivity is poor, with a thermal conductivity coefficient of only 0.2-0.4 W / (m·K). In order to improve their application in new energy vehicle charging cables, it is necessary to improve the thermal conductivity of the material. At present, the research on how to improve the thermal conductivity of polymer materials mostly adopts the method of filling with high thermal conductivity fillers. Studies have shown that the thermal conductivity of composite materials can be improved by increasing the amount of thermal conductive fillers, but a significant increase in the amount of fillers inside the material will also cause the mechanical properties of the material to drop sharply, which cannot meet the use requirements [Yu Pinxuan, Mao Lin, Wang Jinhe. Research on the performance of high-strength thermal conductive EPDM rubber composite materials [J]. Insulation Materials, 2021, 54(6): 6.]. The thermal conductivity of the material can be greatly improved by controlling the orientation distribution of the thermal conductive filler inside the composite material to form a thermal conductive network, and high thermal conductive polymers can be prepared at a lower filling amount. Xia Ru's team at Anhui University added thermal conductive fillers to the blended material. Through process control, the thermal conductive fillers were distributed only in a continuous phase to form a double percolation structure. With the formation of the double percolation structure, the high thermal conductive particles can be selectively distributed in one phase of the blend, thereby forming a more efficient thermal conduction path. While improving the thermal conductivity, the particle filling content is effectively reduced, and a high thermal conductivity composite material is achieved at a low filling dosage, but the other properties cannot meet the requirements of cable materials [Polymer Testing, 2019, 78 (1), 105978]. At present, how to prepare a high thermal conductivity insulation material that meets the requirements of new energy vehicle charging pile cable materials is still a difficult problem. High thermal conductivity can be achieved by adding high-filling thermal conductive fillers to the composite material, but other properties such as mechanics, insulation and aging resistance are often difficult to meet application requirements. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the existing filling type thermally conductive insulating composite material preparation process technology. Through formula design, EPDM rubber and polyethylene form a dual continuous phase structure, and the preparation process is controlled to distribute the thermally conductive filler in the EPDM rubber continuous phase. Since the thermally conductive filler is only dispersed in the EPDM rubber continuous phase, the thermally conductive filler can form a more efficient thermal conductive path therein, greatly improving the thermal conductivity of the composite material. At the same time, adding polyethylene can also improve the mechanical properties of the material, thereby obtaining a high thermal conductivity insulating composite material with high thermal conductivity, high insulation, certain mechanical properties and a simple preparation process. Its performance meets the performance requirements of wire and cable insulation materials and can be widely used in DC charging pile cables for new energy vehicles.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A PE / EPDM high thermal conductivity insulation material for EV charging cables and a preparation method thereof, comprising the following components in parts by weight:
[0007]
[0008] The preparation steps of the above-mentioned high thermal conductivity insulation composite material are as follows:
[0009] S1) weighing each material according to the designed ratio, first adding EPDM raw rubber, stearic acid, zinc oxide, plasticizer, and antioxidant into an internal mixer in sequence for mixing, the mixing temperature is 90-110° C., the mixing time is 3-5 min, and then adding a thermal conductive filler and mixing for 1-2 min, and then discharging the glue to obtain an EPDM masterbatch;
[0010] S2) adding polyethylene to an internal mixer for secondary mixing at a mixing temperature of 120 to 140° C. for a mixing time of 2 to 3 minutes, then adding the EPDM masterbatch prepared in S1) and continuing mixing for 3 to 5 minutes before discharge;
[0011] S3) Place the rubber batch in an open mixing mill preheated to 90°C, add the vulcanizing agent and the vulcanizing agent in sequence and mix for 1 to 2 minutes. After the additives are completely mixed into the rubber compound, make triangle packages 10 times, and thin pass 4 times before producing sheets. Thin pass is the thin pass plastication method, which specifically refers to the process of thinning the rubber compound during the rubber mixing process.
[0012] S4) putting the mixed rubber into a mold and placing it in a flat vulcanizer for vulcanization at a pressure of 15 MPa and a temperature of 160-180° C. for 15 minutes. After vulcanization, a thermally conductive insulating composite material can be obtained.
[0013] The EPDM rubber preferably has an ethylene content of 60-70 wt %, a Mooney viscosity ML 1+4, 100° C. of 40-50, and an ENB content of the third monomer of 3-5 wt %.
[0014] The polyethylene preferably has a melt index of 2.0 to 2.5 g / 10 min.
[0015] The plasticizer is preferably a paraffin-based rubber plasticizer with a viscosity (40° C.) greater than 400 mPa·s and a flash point greater than 240° C.
[0016] The antioxidant is preferably one or more of 2-mercaptobenzimidazole, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and N-cyclohexyl-N′-phenyl-p-phenylenediamine;
[0017] The thermally conductive filler is preferably one or more of aluminum oxide, magnesium oxide, zinc oxide, boron nitride, and aluminum nitride;
[0018] The vulcanizing agent is a peroxide vulcanizing agent, preferably one or more of dicumyl peroxide, diisopropyl peroxide, benzoyl peroxide, and tert-butyl perbenzoate;
[0019] The co-vulcanizing agent is preferably one or more of triallyl isocyanurate, triallyl cyanurate, N,N′-m-phenylene bismaleimide, and N,N′-m-phenylene bismaleimide;
[0020] The formula design of the present invention enables EPDM rubber and polyethylene to form a dual-continuous phase structure, and the preparation process is controlled to distribute the thermally conductive filler in the EPDM rubber continuous phase. Since the thermally conductive filler is only dispersed in the EPDM rubber continuous phase, the thermally conductive filler can form a more efficient thermal conductive path therein, thereby achieving the purpose of significantly improving the thermal conductivity while ensuring the insulation performance of the composite material. The performance of the prepared composite material meets the performance requirements of the insulation layer of wires and cables, and can be widely used in DC charging pile cables for new energy vehicles. There is no report on the preparation method of similar high thermal conductivity insulating composite materials for the insulation layer of wires and cables.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention controls the distribution of the thermally conductive filler in the EPDM continuous phase through formulation and process design, and the thermally conductive filler can form a more efficient thermal conductive path therein, and the prepared thermally conductive insulating composite material has better thermal conductive and insulating properties;
[0023] 2. The polymer-based composite material of the present invention selects a polyethylene / ethylene propylene diene monomer blend system, which effectively solves the problem of poor mechanical properties of the polymer-based composite material after adding a high-filling thermal conductive filler. The composite material still has good mechanical properties when a high amount of thermal conductive filler is added;
[0024] 3. The performance of the thermally conductive composite filler described in the present invention meets the performance requirements of the insulation layer of wires and cables, and can be widely used in DC charging pile cables for new energy vehicles. The preparation process is simple and can be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a flowchart of a method for preparing a PE / EPDM high thermal conductivity insulation material for EV charging cables. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0027] The present invention discloses a PE / EPDM high thermal conductivity insulation material for EV charging cables, wherein the thermal conductive insulation composite material is composed of the following components in parts by weight:
[0028]
[0029] The EPDM rubber has an ethylene content of 60-70 wt %, a Mooney viscosity ML 1+4, 100° C. of 40-50, and a third monomer ENB content of 3-5 wt %.
[0030] The polyethylene has a melt index of 2.0 to 2.5 g / 10 min.
[0031] The plasticizer is a paraffin-based rubber plasticizer with a viscosity (at 40°C) greater than 400 mPa·s and a flash point greater than 240°C.
[0032] The antioxidant is one or more of 2-thiol benzimidazole, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and N-cyclohexyl-N′-phenyl-p-phenylenediamine.
[0033] The thermal conductive filler is one or more of aluminum oxide, magnesium oxide, zinc oxide, boron nitride, and aluminum nitride.
[0034] The vulcanizing agent is one or more of dicumyl peroxide, dicumyl peroxide, benzoyl peroxide, and tert-butyl perbenzoate.
[0035] The auxiliary vulcanizing agent is one or more of triallyl isocyanurate, triallyl cyanurate, N,N′-m-phenylene bismaleimide, and N,N′-m-phenylene bismaleimide.
[0036] like Figure 1 As shown, the present invention provides a method for preparing the above-mentioned thermally conductive insulating composite material, the method specifically comprising the following steps:
[0037] S1) weighing each material according to the designed ratio, first adding EPDM raw rubber, stearic acid, zinc oxide, plasticizer, and antioxidant into an internal mixer in sequence for mixing, the mixing temperature is 90-110° C., the mixing time is 3-5 min, and then adding a thermal conductive filler and mixing for 1-2 min, and then discharging the glue to obtain an EPDM masterbatch;
[0038] S2) adding polyethylene to an internal mixer for secondary mixing at a mixing temperature of 120 to 140° C. for a mixing time of 2 to 3 minutes, then adding the EPDM masterbatch prepared in S1) and continuing mixing for 3 to 5 minutes before discharge;
[0039] S3) placing the rubber batch in an open mill preheated to 90°C, adding the vulcanizing agent and the vulcanizing agent in sequence and milling for 1 to 2 minutes, after the additives are completely mixed into the rubber batch, making triangle packages 10 times, and thinning through 4 times before producing the sheet;
[0040] S4) putting the mixed rubber into a mold and placing it in a flat vulcanizer for vulcanization at a pressure of 15 MPa and a temperature of 160-180° C. for 15 minutes. After vulcanization, a thermally conductive insulating composite material can be obtained.
[0041] The obtained thermally conductive insulating composite material has a thermal conductivity of 1.03-1.29 W / (m·K), a tensile strength of 8.47-10.92 MPa, and a volume resistivity of 8.73×10 14 -9.24×10 14 Ω·cm.
[0042] Example 1
[0043] (1) 10.40 parts by mass of EPDM rubber, 0.10 parts by mass of stearic acid, 0.52 parts by mass of zinc oxide, 3.1 parts by mass of TUDALEN 13, and 0.10 parts by mass of 2-mercaptobenzimidazole were sequentially added into an internal mixer and mixed at 100° C. for 3 min. 75.00 parts by mass of aluminum oxide were added and mixed for 1 min. The EPDM masterbatch was obtained by rubber removal.
[0044] (2) 10.40 parts by weight of polyethylene was added to an internal mixer and mixed at 130° C. for 3 min. 89.22 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0045] (3) Place the discharged rubber in a 90°C open mill, add 0.16 parts by mass of butyl peroxide diisopropylbenzene and 0.22 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make a triangle bag 10 times, and thin pass 4 times before making a sheet. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15 MPa and a temperature of 170°C. Keep the temperature and pressure for 15 minutes. After the vulcanization is completed, open the mold and take it out.
[0046] Example 2
[0047] (1) 12.47 parts by mass of EPDM rubber, 0.13 parts by mass of stearic acid, 0.62 parts by mass of zinc oxide, 3.74 parts by mass of TUDALEN 13, and 0.13 parts by mass of 2-mercaptobenzimidazole were sequentially added into an internal mixer and kneaded at 100° C. for 3 min. 70.00 parts by mass of boron nitride was added and kneaded for 1 min. The EPDM masterbatch was obtained by debonding.
[0048] (2) 12.47 parts by weight of polyethylene was added to an internal mixer and mixed at 100° C. for 3 min. 87.09 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0049] (3) Place the discharged rubber in a 90°C open mill, add 0.19 parts by mass of butyl peroxide diisopropylbenzene and 0.25 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make triangle packages 10 times, thin pass 4 times and then produce sheets. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, open the mold and take it out.
[0050] Example 3
[0051] (1) 10.40 parts by mass of EPDM rubber, 0.10 parts by mass of stearic acid, 0.52 parts by mass of zinc oxide, 3.10 parts by mass of TUDALEN 13, and 0.10 parts by mass of 2-mercaptobenzimidazole were sequentially added into an internal mixer and kneaded at 100° C. for 3 min. 20.00 parts by mass of boron nitride and 55.00 parts by mass of aluminum oxide were sequentially added and kneaded for 1 min. The EPDM masterbatch was obtained by debonding.
[0052] (2) 10.40 parts by weight of polyethylene was added to an internal mixer and mixed at 100° C. for 3 min. 89.22 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0053] (3) Place the discharged rubber in a 90°C open mill, add 0.16 parts by mass of butyl peroxide diisopropylbenzene and 0.22 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make triangle packages 10 times, thin pass 4 times and then produce sheets. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, open the mold and take it out.
[0054] Example 4
[0055] (1) 10.40 parts by mass of EPDM rubber, 0.10 parts by mass of stearic acid, 0.52 parts by mass of zinc oxide, 3.10 parts by mass of TUDALEN 13, and 0.10 parts by mass of 2-mercaptobenzimidazole were sequentially added into an internal mixer and kneaded at 100° C. for 3 min. 25.00 parts by mass of boron nitride and 50.00 parts by mass of aluminum oxide were sequentially added and kneaded for 1 min. The EPDM masterbatch was obtained by debonding.
[0056] (2) 10.40 parts by weight of polyethylene was added to an internal mixer and mixed at 100° C. for 3 min. 89.22 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0057] (3) Place the discharged rubber in a 90°C open mill, add 0.16 parts by mass of butyl peroxide diisopropylbenzene and 0.22 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make triangle packages 10 times, thin pass 4 times and then produce sheets. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, open the mold and take it out.
[0058] Example 5
[0059] (1) 12.47 parts by mass of EPDM rubber, 0.13 parts by mass of stearic acid, 0.62 parts by mass of zinc oxide, 3.74 parts by mass of TUDALEN 13, and 0.13 parts by mass of 2-mercaptobenzimidazole were sequentially added into an internal mixer and kneaded at 100° C. for 3 min. 20.00 parts by mass of boron nitride and 50.00 parts by mass of aluminum oxide were sequentially added and kneaded for 1 min. The EPDM masterbatch was obtained by debonding.
[0060] (2) 12.47 parts by weight of polyethylene was added to an internal mixer and mixed at 100° C. for 3 min. 87.09 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0061] (3) Place the discharged rubber in a 90°C open mill, add 0.19 parts by mass of butyl peroxide diisopropylbenzene and 0.25 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make triangle packages 10 times, thin pass 4 times and then produce sheets. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, open the mold and take it out.
[0062] Example 6
[0063] (1) 12.47 parts by mass of EPDM rubber, 0.13 parts by mass of stearic acid, 0.62 parts by mass of zinc oxide, 3.74 parts by mass of TUDALEN 13, and 0.13 parts by mass of 2-mercaptobenzimidazole were added to an internal mixer in sequence and mixed at 100° C. for 3 min. 25.00 parts by mass of boron nitride and 45.00 parts by mass of aluminum oxide were added in sequence and mixed for 1 min. The EPDM masterbatch was obtained by debonding.
[0064] (2) 12.47 parts by weight of polyethylene was added to an internal mixer and mixed at 100° C. for 3 min. 87.09 parts by weight of EPDM masterbatch was added and mixed for another 3 min before discharge.
[0065] (3) Place the discharged rubber in a 90°C open mill, add 0.19 parts by mass of butyl peroxide diisopropylbenzene and 0.25 parts by mass of triallyl isocyanurate in sequence, and after the additives are completely mixed into the rubber, make triangle packages 10 times, thin pass 4 times and then produce sheets. Put the mixed rubber into a mold and place it in a flat vulcanizer for vulcanization at a pressure of 15MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, open the mold and take it out.
[0066] Performance Test:
[0067] The materials prepared in Examples 1-6 were tested for thermal conductivity, mechanical properties, and aging resistance, and the results are as follows:
[0068] Table 1 Test results
[0069]
[0070]
[0071]
[0072] It can be seen from Table 1 that the insulating materials prepared in Examples 1-6 have high thermal conductivity, and the mechanical properties, insulation properties and heat aging resistance all meet the requirements, and are suitable for use in new energy vehicle charging pile cables.
[0073] The embodiment of the present application provides a PE / EPDM high thermal conductivity insulation material and preparation method for EV charging cables, which are introduced in detail. The description of the above embodiments is only used to help understand the method and core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
[0074] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problems within a preset error range and basically achieve the technical effects. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be subject to that defined in the attached claims.
[0075] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0076] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0077] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. A method for preparing PE / EPDM high thermal conductivity insulation material for EV charging cables, characterized in that: The PE / EPDM high thermal conductivity insulation material is composed of the following components in parts by weight: 10.00~15.00 parts of EPDM rubber; 0.10-0.15 parts of stearic acid; Zinc oxide 0.50~0.75 parts; Plasticizer 3.00~4.50 parts; Antiaging agent 0.10~0.15 parts; Thermal conductive filler 70.00~75.00 parts; Polyethylene 10.00~15.00 parts; 0.30~0.45 parts of vulcanizing agent; Curing agent 0.15~0.23 parts; The thermal conductive filler is one or more of aluminum oxide, magnesium oxide, zinc oxide, boron nitride, and aluminum nitride; The EPDM rubber has an ethylene content of 60-70wt%, a Mooney viscosity of ML 1+4 at 100°C of 40-50, and a third monomer ENB content of 3-5wt%; The polyethylene has a melt index of 2.0-2.5 g / 10min; the method specifically comprises the following steps: S1) weighing each material according to the designed ratio, first adding EPDM raw rubber, stearic acid, zinc oxide, plasticizer, and antioxidant into an internal mixer in sequence for mixing, the mixing temperature is 90-110°C, the mixing time is 3-5 min, then adding a thermal conductive filler and mixing for 1-2 min, and then discharging the glue to obtain an EPDM masterbatch; S2) polyethylene is then added to the internal mixer for secondary mixing at a mixing temperature of 120-140°C for 2-3 min, and then the EPDM masterbatch prepared in S1) is added and mixed for 3-5 min before discharge; S3) Place the rubber batch in an open mixer preheated to 90°C, add the vulcanizing agent and the vulcanizing agent in turn and mix for 1 to 2 minutes. After the additives are completely mixed into the rubber batch, make a triangle bag 10 times, and thin it 4 times before making a sheet. S4) Put the mixed rubber into the mold and place it in a flat vulcanizer for vulcanization at a pressure of 15 MPa and a temperature of 160-180°C. Keep the temperature and pressure for 15 minutes. After vulcanization, a high thermal conductivity insulating material can be obtained. The obtained high thermal conductivity insulating material has a thermal conductivity of 1.03-1.29 W / (m·K), a tensile strength of 8.47-10.92 MPa, and a volume resistivity of .
2. The preparation method according to claim 1, characterized in that: The plasticizer is a paraffin-based rubber plasticizer with a viscosity greater than 400 mPa·s at 40°C and a flash point greater than 240°C.
3. The preparation method according to claim 1, characterized in that: The antioxidant is one or more of 2-thiol benzimidazole, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and N-cyclohexyl-N′-phenyl-p-phenylenediamine.
4. The preparation method according to claim 1, characterized in that: The vulcanizing agent is one or more of dicumyl peroxide, di-tert-butyl dicumyl peroxide, benzoyl peroxide, and tert-butyl perbenzoate.
5. The preparation method according to claim 1, characterized in that: The auxiliary vulcanizing agent is one or more of triallyl isocyanurate, triallyl cyanurate, N,N′-m-phenylene bismaleimide, and N,N′-m-phenylene bismaleimide.
Citation Information
Patent Citations
Heat-conduction electric-insulation rubber-plastic composite material and preparation method thereof
CN104893307A
Ethylene-propylene-diene monomer insulating material with high mechanical property and preparation method thereof
CN114516990A